OPTIMASI SMART FARMING HYDROPONIC NFT SYSTEM PADA BUDIDAYA TANAMAN PAKCOY SHANGHAI BERBASIS INTERNET OF THINGS MENGGUNAKAN ARDUINO UNO R4 WIFI - Toni Rahmat Wahyu; Ade Sumaedi (Infotech: Journal of Technology Information, 2025)
This study aims to develop a Smart Farming Hydroponic system based on IoT (Internet of Things) technology using the NFT (Nutrient Film Technique) for cultivating Shanghai Pakcoy. Utilizing the Arduino UNO R4 WiFi as the main microcontroller, the research integrates TDS and pH sensors to enable real-time monitoring of AB mix nutrient levels and water acidity. All data collected by the system is processed using the Arduino Cloud IoT Remote platform, allowing for remote monitoring and automated control. The study is conducted in Kampung Buah Tilu, Desa Cisaat Padarincang, focusing on optimizing limited land use in rural areas to introduce modern agricultural technology. The system is designed to enhance cultivation efficiency by maintaining nutrient and pH parameters within optimal ranges for plant growth. Additionally, the scope of the research is limited to technical aspects of nutrient management, excluding temperature and humidity control. The findings indicate that the Smart Farming Hydroponic NFT (Nutrient Film Technique) system successfully improves cultivation efficiency, provides real-time data visualization, and ensures optimal conditions for Shanghai Pakcoy growth. This research not only offers an efficient and eco-friendly agricultural solution but also opens up opportunities for developing similar technologies to empower rural communities. Through this innovation, IoT (Internet of Things) technology can be applied to sustainable farming systems to enhance productivity and improve agricultural product quality.